Identification of biomarkers for endometriosis in plasma from patients with endometriosis using a proteomics approach - Hwang, Jin-Hee; Lee, Kyu-Sup; Joo, Jong-Kil; Wang, Tao; Son, Jung-Bin; Park, Jung-Ha; Hwang, Dae-Youn; Choi, Man-Ho; Lee, Hong-Gu (SPANDIDOS PUBL LTD, 2014)
The present study aimed to examine potential biomarkers for the diagnosis of endometriosis. A plasma-based proteomic approach, including 2-dimentional electrophoresis and mass spectrometry, was used. Samples were obtained from patients with (n=15) and without (n=15) endometriosis, or from mice with surgically induced endometriosis. Seven spots corresponding to six differentially expressed proteins were identified in the human plasma samples. However, only haptoglobin (Hp) was identified to be significantly decreased in the plasma levels of patients with endometriosis (P<0.05) and in mice with surgically induced endometriosis (P<0.05). The results demonstrated that Hp was downregulated in females with endometriosis, and it therefore, may be a useful diagnostic tool as a biomarker of endometriosis.
Keywords: OXIDATIVE STRESS; MICROARRAY ANALYSIS; SERUM MARKER; EXPRESSION; DIAGNOSIS; AUTOANTIBODY; CA-125; FLUID; CELLS; WOMEN